PENGARUH IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 35 TAHUN 2023 TERHADAP PELAYANAN RETRIBUSI PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN AGAM TAHUN 2023-2024 - Murni, Indah Yuliza; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
January 5, 2024, Agam Regency will begin to carry out free Motor Vehicle Testing, which is in accordance with the issuance of Government Regulation Number 35 of 2023 concerning General Provisions for Regional Taxes and Regional Levies. The regulation no longer orders the levy to be levied on Motor Vehicle Testing/KIR. With the removal of the levy on Motor Vehicle Testing, it will affect many aspects including service aspects. Therefore, a study was conducted to see how the implementation of Government Regulation Number 35 of 2023 affects motor vehicle testing services in Agam Regency in 2024. This study aims to understand the influence of the implementation of the elimination of the motor vehicle testing levy on its services at the Agam Regency Transportation Office. This research was conducted with a qualitative descriptive approach. By using the main theory, namely the theory of policy implementation by Charles O Jones with 3 indicators, namely Organization, Interpretation and Application of policies. The results of this study show that the implementation of Government Regulation number 35 of 2023 for motor vehicle testing servers does not have a major effect. The implementation of the regulation only reduces the stages in motor vehicle testing which were initially 3 stages, namely the administrative registration stage, the payment stage, and the testing stage and the acceptance of test results then to 2 stages, namely the administrative registration stage and the testing stage and the acceptance of test results. Another influence is on the original regional income which is no longer obtained from the motor vehicle testing levy revenue post. From these results, it is hoped that the implementation of the policy will not reduce service performance at the Agam Regency Transportation Office. Keywords: Implementation, Policy, Service, Testing Vehicle Motorized